Volatility in an era of reduced uncertainty: Lessons from Pax Britannica - Brown, William O.; Burdekin, Richard C.K.; Weidenmier, Marc D. (Journal of Financial Economics, 2006)
Although it has been well established that financial volatility is related to news and macroeconomic shocks, less emphasis has been placed on the importance of underlying economic and political stability. In this paper we study the behavior of consol returns since 1729 and identify a greater-than-50% decline in volatility from the end of the Napoleonic Wars in 1815 until the First World War. News events and macroeconomic variables cannot account for this extended period of reduced volatility. Underlying political stability under Pax Britannica seems to be a more likely explanation.